STRATEGIC VEHICLES IMPORT SUPPLY CHAIN: A PARADIGM SHIFT IN AUSTRALIAN AUTOMOTIVE INDUSTRY - Kristina Malihi; Himanshu Shee (Asian Academy of Management Journal, 2017)
This study aims to formulate a buffer stock-adjusted make-to-stock (MTS) parts forecasting heuristic, which has the potential to ease the tight dispatch lead time issue facing first tier suppliers in vehicles import supply chain. The research is motivated by an issue of justin- time (JIT) parts dispatch to auto companies partly due to inadequate lead time given to the first tier suppliers. Compiling secondary data from industry sources, we estimated the overseas shipment time and parts dispatch lead time while developing heuristics to forecast vehicles parts requirement with due care for buffer stock. Results suggest a strategic hybrid approach combining MTS parts ordering with JIT supply to auto manufacturers. MTS will help first tier suppliers to source and stock parts in-house that can be supplied just in time to help completing vehicle fitment. This approach is likely to ease the lead time pressure of first tier suppliers without affecting JIT supply to the automotive companies. The study concludes with theoretical and practical implications for Australian first tier parts importers as well as automotive companies.